Analysis Monetary System Development International, Loan and Investment Foreign and Multinational - Era Mustika; Fildzah Darayanti Mujasmara; Santi Melati; Khairani Matondang; Riza Indrani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Foreign direct investment in Indonesia is influenced by various factors. The main goal of studies this is for knowing how influence connection growth economy, the international monetary system against foreign direct investment (FDI) and multinational. Data obtained from official internet sites. System changes the other system was caused by the economic turmoil at that time. To this very day the international monetary system is still a concern of all countries and still want change the system Becomes more function optimal. For that writer will discuss related with